Ultrahigh Performance Nanoengineered Graphene–Concrete Composites for Multifunctional Applications. (23rd April 2018) - Dimov, Dimitar; Amit, Iddo; Gorrie, Olivier; Barnes, Matthew D.; Townsend, Nicola J.; Neves, Ana I. S.; Withers, Freddie; Russo, Saverio; Craciun, Monica Felicia
Abstract: There is a constant drive for development of ultrahigh performance multifunctional construction materials by the modern engineering technologies. These materials have to exhibit enhanced durability and mechanical performance, and have to incorporate functionalities that satisfy multiple uses in order to be suitable for future emerging structural applications. There is a wide consensus in the research community that concrete, the most used construction material worldwide, has to be engineered at the nanoscale, where its chemical and physiomechanical properties can be truly enhanced. Here, an innovative multifunctional nanoengineered concrete showing an unprecedented range of enhanced properties when compared to standard concrete, is reported. These include an increase of up to 146% in the compressive and 79.5% in the flexural strength, whilst at the same time an enhanced electrical and thermal performance is found. A surprising decrease in water permeability by nearly 400% compared to normal concrete makes this novel composite material ideally suitable for constructions in areas subject to flooding. The unprecedented gamut of functionalities that are reported in this paper are produced by the addition of water‐stabilized graphene dispersions, an advancement in the emerging field of nanoengineered concrete which can be readily applied in a more sustainable construction industry. Abstract : A novel method for reinforcing concrete with high‐quality graphene dispersions leads to unprecedented increase in all fundamental mechanical properties. The addition of graphene makes concrete 146% stronger and decreases its water permeability by 400%. These improvements can lead to significant reduction of carbon emissions, due to cement production, which will have a drastic positive effect on global climate change.